Development of a dental tourism management system: Rent A Dent - Jezdovic, Ivan; Popović, Snežana; Plavljanic, Aleksandar; Antic, Danica (E-business technologies conference proceedings, 2021)
The popular term that defines the act of traveling abroad to obtain desired dental care is called dental tourism. The following problems that arise with this occurrence are transparency in dental processes, data confidentiality, insurance problems and credibility of dental clinics. With technology getting more advanced every day, it became easier for patients to find appropriate dental care with numerous platforms that connect patients with desired dental care professionals. Rent A Dent represents a platform that allows patients to explore dental clinics abroad, giving them all the information they need. When the desired clinic is chosen by the patient, Rent a Dent platform acts as an intermediary between them to assure that both parties are satisfied and that the agreed dental services have been rendered.